Peran Pemerintah Selandia Baru dalam Memulihkan Perdamaian dan Persatuan Pasca Tragedi Christchurch - dian ayu; Herlina Juni Risma Saragih; I Gede Sumertha KY; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The role of the New Zealand government in restoring peace and unity after the Christchurch tragedy is an important matter to study. What is unique about the role of the country's government is that its response is inclusive and flexible, focusing on healing and progress rather than revenge. This study uses qualitative analysis methods, including data condensation, data display, and drawing and verifying conclusions. Data was obtained through literature study and interviews or interactive discussions during Overseas Work Lecture activities. This study aims to provide a description of the government's role in restoring peace and unity after the tragedy. The New Zealand government's response involved collaboration between three levels of the conceptual approach to peacebuilding proposed by Lederach in 1997. These levels include the Top-Level Approach, the Mid-Level Approach and the Grassroots Approach. The findings of this study are that the government's response included the Arms (Prohibited Firearms, Magazines and Parts) Amendment Bill, which became the Arms Legislation Bill on 23 June 2020 the Governor-General formally signed the Bill into law, and the implementation of the Christchurch Call, while the community provided support and initiatives for mental health and solidarity. This article also suggests that Indonesia can learn from New Zealand's response and recommends implementing a national security law. This research emphasizes the importance of coordination and collaboration between actors at various levels in building peace and unity after a tragedy.